Cross-Sector Responses to Obesity: Models for Change: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Obesity affects 17 percent of children and adolescents and almost 36 percent of adults in the United States. Conservative estimates suggest that obesity now accounts for almost 20 percent of national health care spending. Until the obesity epidemic is reversed, obesity will continue to drive rates of chronic diseases such as heart disease, stroke, type 2 diabetes, and certain types of cancer. Cross-Sector Responses to Obesity is a summary of a workshop convened by the Institute of Medicine Roundtable on Obesity Solutions in September 2014 to explore models of cross-sector work that may reduce the prevalence and consequences of obesity. This report identifies case studies of cross-sector initiatives that engage partners from diverse fields, and lessons learned from and barriers to established cross-sector initiatives.
Keywords: Food and Nutrition; Health and Medicine

Evaluating Obesity Prevention Efforts: A Plan for Measuring Progress - Institute of Medicine (The National Academies Press, 2013)
Obesity poses one of the greatest public health challenges of the 21st century, creating serious health, economic, and social consequences for individuals and society. Despite acceleration in efforts to characterize, comprehend, and act on this problem, including implementation of preventive interventions, further understanding is needed on the progress and effectiveness of these interventions. Evaluating Obesity Prevention Efforts develops a concise and actionable plan for measuring the nation's progress in obesity prevention efforts—specifically, the success of policy and environmental strategies recommended in the 2012 IOM report Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation. This book offers a framework that will provide guidance for systematic and routine planning, implementation, and evaluation of the advancement of obesity prevention efforts. This framework is for specific use with the goals and strategies from the 2012 report and can be used to assess the progress made in every community and throughout the country, with the ultimate goal of reducing the obesity epidemic. It offers potentially valuable guidance in improving the quality and effect of the actions being implemented. The recommendations of Evaluating Obesity Prevention Efforts focus on efforts to increase the likelihood that actions taken to prevent obesity will be evaluated, that their progress in accelerating the prevention of obesity will be monitored, and that the most promising practices will be widely disseminated.
Keywords: Food and Nutrition; Health and Medicine

Cross-Sector Responses to Obesity: Models for Change: Workshop in Brief - Institute of Medicine (The National Academies Press, 2014)
On September 30, 2014, the Institute of Medicine's Roundtable on Obesity Solutions held a 1-day workshop titled "Cross-Sector Work on Obesity Prevention, Treatment, and Weight Maintenance: Models for Change." The workshop was designed to explore models of cross-sector work that may reduce the prevalence and consequences of obesity, discuss lessons learned from case studies of cross-sector initiatives, and spur future cross-sector collaboration. This brief summary of the workshop highlights the salient points that emerged from the presentations and discussions at the workshop.
Keywords: Food and Nutrition

Local Government Actions to Prevent Childhood Obesity - Transportation Research Board; Institute of Medicine; National Research Council (The National Academies Press, 2009)
The prevalence of childhood obesity is so high in the United States that it may reduce the life expectancy of today's generation of children. While parents and other adult caregivers play a fundamental role in teaching children about healthy behaviors, even the most positive efforts can be undermined by local environments that are poorly suited to supporting healthy behaviors. For example, many communities lack ready sources of healthy food choices, such as supermarkets and grocery stores. Or they may not provide safe places for children to walk or play. In such communities, even the most motivated child or adolescent may find it difficult to act in healthy ways. Local governments—with jurisdiction over many aspects of land use, food marketing, community planning, transportation, health and nutrition programs, and other community issues—are ideally positioned to promote behaviors that will help children and adolescents reach and maintain healthy weights. Local Government Actions to Prevent Childhood Obesity presents a number of recommendations that touch on the vital role of government actions on all levels—federal, state, and local—in childhood obesity prevention. The book offers healthy eating and physical activity strategies for local governments to consider, making it an excellent resource for mayors, managers, commissioners, council members, county board members, and administrators.
Keywords: Health and Medicine; Food and Nutrition

Driving Action and Progress on Obesity Prevention and Treatment: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
After decades of increases in the obesity rate among U.S. adults and children, the rate recently has dropped among some populations, particularly young children. What are the factors responsible for these changes? How can promising trends be accelerated? What else needs to be known to end the epidemic of obesity in the United States? To examine these and other pressing questions, the Roundtable on Obesity Solutions, of the National Academies of Sciences, Engineering, and Medicine, held a workshop in September 2016. The workshop brought together leaders from business, early care and education, government, health care, and philanthropy to discuss the most promising approaches for the future of obesity prevention and treatment. This publication summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Strategies to Limit Sugar-Sweetened Beverage Consumption in Young Children: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
On June 21–22, 2017, the National Academies of Sciences, Engineering, and Medicine’s Food and Nutrition Board convened a workshop in Washington, DC, to explore the range of policies and programs that exist at the federal, state, tribal, and local levels to limit sugar-sweetened beverage consumption in children birth to 5 years of age. Topics examined over the course of the 1.5-day workshop included prevalence and trends in beverage intake among young children; beverage intake guidelines applicable to the age range of interest; challenges and opportunities of influencing beverage consumption; the role of industry in beverage intake; and knowledge gaps and research needs. This publication highlights key points made by individual speakers during the presentations and discussions.
Keywords: Food and Nutrition; Health and Medicine

Community Perspectives on Obesity Prevention in Children: Workshop Summaries - Institute of Medicine (The National Academies Press, 2009)
As the public health threat of childhood obesity has become clear, the issue has become the focus of local, state, and national initiatives. Many of these efforts are centered on the community environment in recognition of the role of environmental factors in individual behaviors related to food and physical activity. In many communities, for example, fresh produce is not available or affordable, streets and parks are not amenable to exercise, and policies and economic choices make fast food cheaper and more convenient than healthier alternatives. Community efforts to combat obesity vary in scope and scale; overall, however, they remain fragmented, and little is known about their effectiveness. At the local level, communities are struggling to determine which obesity prevention programs to initiate and how to evaluate their impact. In this context, the Institute of Medicine held two workshops to inform current work on obesity prevention in children through input from individuals who are actively engaged in community- and policy-based obesity prevention programs. Community perspectives were elicited on the challenges involved in undertaking policy and programmatic interventions aimed at preventing childhood obesity, and on approaches to program implementation and evaluation that have shown promise. Highlights of the workshop presentations and discussions are presented in this volume.
Keywords: Health and Medicine; Food and Nutrition

Obesity in the Early Childhood Years: State of the Science and Implementation of Promising Solutions: Workshop in Brief - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On October 6, 2015, the Roundtable on Obesity Solutions of the National Academies of Sciences, Engineering, and Medicine held a workshop titled "Obesity in the Early Childhood Years: State of the Science and Implementation of Promising Solutions." The workshop examined what is currently known about the prevalence of obesity in young children, its trends over time, and its persistence into later childhood, adolescence, and adulthood; epigenetic factors related to risk of early childhood obesity; and the development of taste and flavor preferences in the first few years of life. The workshop explored recent developments in the science of modifiable protective and risk factors associated with obesity through age 5, including a mother's pre-pregnancy weight and weight gain during pregnancy; smoking during pregnancy; breastfeeding; complementary feeding, responsive parenting; and sleep, activity, and sedentary behavior in young children.
Keywords: Food and Nutrition; Health and Medicine

The Role of Business in Multisector Obesity Solutions: Working Together for Positive Change: Workshop in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On April 12, 2016, the Roundtable on Obesity Solutions convened a 1-day workshop in Washington, DC, to examine the role of the business sector in obesity solutions. The goal of the workshop was threefold: (1) explore why companies should be involved in obesity solutions and how to encourage them to do so; (2) identify reasons why businesses might be interested in being involved in obesity solutions; (3) identify ways in which business can be engaged in obesity solutions. This report highlights key points made during the presentations and discussions at the workshop.
Keywords: Food and Nutrition

The Current State of Obesity Solutions in the United States: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
For the first time in decades, promising news has emerged regarding efforts to curb the obesity crisis in the United States. Obesity rates have fallen among low-income children in 18 states, the prevalence of obesity has plateaued among girls, regardless of ethnicity, and targeted efforts in states such as Massachusetts have demonstrably reduced the prevalence of obesity among children. Although the reasons for this turnaround are as complex and multifaceted as the reasons for the dramatic rise in obesity rates in recent decades, interventions to improve nutrition and increase physical activity are almost certainly major contributors. Yet major problems remain. Diseases associated with obesity continue to incur substantial costs and cause widespread human suffering. Moreover, substantial disparities in obesity rates exist among population groups, and in some cases these disparities are widening. Some groups and regions are continuing to experience increases in obesity rates, and the prevalence of severe obesity is continuing to rise. The Current State of Obesity Solutions in the United States is the summary of a workshop convened in January 2014 by the Institute of Medicine Roundtable on Obesity Solutions to foster an ongoing dialogue on critical and emerging implementation, policy, and research issues to accelerate progress in obesity prevention and care. Representatives of public health, health care, government, the food industry, education, philanthropy, the nonprofit sector, and academia met to discuss interventions designed to prevent and treat obesity. The workshop focused on early care and education, schools, worksites, health care institutions, communities and states, the federal government, and business and industry. For each of these groups, this report provides an overview of current efforts to improve nutrition, increase physical activity, and reduce disparities among populations.
Keywords: Food and Nutrition; Health and Medicine

Physical Activity: Moving Toward Obesity Solutions: Workshop in Brief - Institute of Medicine (The National Academies Press, 2015)
On April 14-15, 2015, the Roundtable on Obesity Solutions held a 2-day workshop titled "Physical Activity: Moving Toward Obesity Solutions." The goal of the workshop was to provide an expert summary of the state of the science regarding the impact of physical activity in the prevention and treatment of overweight and obesity and to highlight innovative strategies for promoting physical activity across segments of the population. This Workshop in Brief highlights key points made during the presentations and discussion.
Keywords: Health and Medicine; Food and Nutrition

Physical Activity: Moving Toward Obesity Solutions: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
In 2008, the U.S. federal government issued fully approved physical activity guidelines for the first time. The idea that physical activity impacts health can be traced as far back as Hippocrates, and the science around the linkages between physical activity and health has continuously accumulated. On April 14-15, 2015, the Institute of Medicine’s Roundtable on Obesity Solutions held a 2-day workshop to explore the state of the science regarding the impact of physical activity in the prevention and treatment of overweight and obesity and to highlight innovative strategies for promoting physical activity across different segments of the population. This report summarizes the presentations and discussions from this workshop.
Keywords: Food and Nutrition; Health and Medicine

Driving Action and Progress on Obesity Prevention and Treatment: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The Roundtable on Obesity Solutions of the Health and Medicine Division of the National Academies of Sciences, Engineering, and Medicine held a workshop in Washington, DC, on September 27, 2016, titled "Driving Action and Progress on Obesity Prevention and Treatment." The workshop was designed to (1) review the progress that has been made in obesity prevention and treatment; (2) identify some of the levers that can drive significant future progress; and (3) discuss how gaps in the field can be filled. This Proceedings of a Workshop-in Brief highlights key points made during the presentations and discussions and is not intended to provide a comprehensive summary of information shared during the workshop.
Keywords: Food and Nutrition

Obesity in the Early Childhood Years: State of the Science and Implementation of Promising Solutions: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Among the many troubling aspects of the rising prevalence of obesity in the United States and elsewhere in recent years, the growth of early childhood overweight and obesity stands out. To explore what is known about effective and innovative interventions to counter obesity in young children, the National Academies of Sciences, Engineering, and Medicine’s Roundtable on Obesity Solutions held a workshop in October 2015. The workshop brought together many of the leading researchers on obesity in young children to describe the state of the science and potential solutions based on that research. Participants explored sustainable collaborations and new insights into the implementation of interventions and policies, particularly those related to nutrition and physical activity, for the treatment and prevention of obesity in young children. Obesity in the Early Childhood Years summarizes the presentations and discussions from the workshop.
Keywords: Food and Nutrition

Assessing Prevalence and Trends in Obesity: Navigating the Evidence - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Obesity has come to the forefront of the American public health agenda. The increased attention has led to a growing interest in quantifying obesity prevalence and determining how the prevalence has changed over time. Estimates of obesity prevalence and trends are fundamental to understanding and describing the scope of issue. Policy makers, program planners, and other stakeholders at the national, state, and local levels are among those who search for estimates relevant to their population(s) of interest to inform their decision-making. The differences in the collection, analysis, and interpretation of data have given rise to a body of evidence that is inconsistent and has created barriers to interpreting and applying published reports. As such, there is a need to provide guidance to those who seek to better understand and use estimates of obesity prevalence and trends. Assessing Prevalence and Trends in Obesity examines the approaches to data collection, analysis, and interpretation that have been used in recent reports on obesity prevalence and trends at the national, state, and local level, particularly among U.S. children, adolescents, and young adults. This report offers a framework for assessing studies on trends in obesity, principally among children and young adults, for policy making and program planning purposes, and recommends ways decision makers and others can move forward in assessing and interpreting reports on obesity trends.
Keywords: Food and Nutrition

Early Childhood Obesity Prevention Policies - Institute of Medicine (The National Academies Press, 2011)
Childhood obesity is a serious health problem that has adverse and long-lasting consequences for individuals, families, and communities. The magnitude of the problem has increased dramatically during the last three decades and, despite some indications of a plateau in this growth, the numbers remain stubbornly high. Efforts to prevent childhood obesity to date have focused largely on school-aged children, with relatively little attention to children under age 5. However, there is a growing awareness that efforts to prevent childhood obesity must begin before children ever enter the school system. Early Childhood Obesity Prevention Policies reviews factors related to overweight and obese children from birth to age 5, with a focus on nutrition, physical activity, and sedentary behavior, and recommends policies that can alter children's environments to promote the maintenance of healthy weight. Because the first years of life are important to health and well-being throughout the life span, preventing obesity in infants and young children can contribute to reversing the epidemic of obesity in children and adults. The book recommends that health care providers make parents aware of their child's excess weight early. It also suggests that parents and child care providers keep children active throughout the day, provide them with healthy diets, limit screen time, and ensure children get adequate sleep. In addition to providing comprehensive solutions to tackle the problem of obesity in infants and young children, Early Childhood Obesity Prevention Policies identifies potential actions that could be taken to implement those recommendations. The recommendations can inform the decisions of state and local child care regulators, child care providers, health care providers, directors of federal and local child care and nutrition programs, and government officials at all levels.
Keywords: Health and Medicine; Food and Nutrition

Measuring Progress in Obesity Prevention: Workshop Report - Institute of Medicine (The National Academies Press, 2012)
Nearly 69 percent of U.S. adults and 32 percent of children are either overweight or obese, creating an annual medical cost burden that may reach $147 billion. Researchers and policy makers are eager to identify improved measures of environmental and policy factors that contribute to obesity prevention. The IOM formed the Committee on Accelerating Progress in Obesity Prevention to review the IOM's past obesity-related recommendations, identify a set of recommendations for future action, and recommend indicators of progress in implementing these actions. The committee held a workshop in March 2011 about how to improve measurement of progress in obesity prevention.
Keywords: Health and Medicine

Accelerating Progress in Obesity Prevention: Solving the Weight of the Nation - Institute of Medicine (The National Academies Press, 2012)
One-third of adults are now obese, and children's obesity rates have climbed from 5 to 17 percent in the past 30 years. The causes of the nation's obesity epidemic are multi-factorial, having much more to do with the absence of sidewalks and the limited availability of healthy and affordable foods than a lack of personal responsibility. The broad societal changes that are needed to prevent obesity will inevitably affect activity and eating environments and settings for all ages. Many aspects of the obesity problem have been identified and discussed; however, there has not been complete agreement on what needs to be done to accelerate progress. Accelerating Progress in Obesity Prevention reviews previous studies and their recommendations and presents five key recommendations to accelerate meaningful change on a societal level during the next decade. The report suggests recommendations and strategies that, independently, can accelerate progress, but urges a systems approach of many strategies working in concert to maximize progress in accelerating obesity prevention. The recommendations in Accelerating Progress in Obesity Prevention include major reforms in access to and opportunities for physical activity; widespread reductions in the availability of unhealthy foods and beverages and increases in access to healthier options at affordable, competitive prices; an overhaul of the messages that surround Americans through marketing and education with respect to physical activity and food consumption; expansion of the obesity prevention support structure provided by health care providers, insurers, and employers; and schools as a major national focal point for obesity prevention. The report calls on all individuals, organizations, agencies, and sectors that do or can influence physical activity and nutrition environments to assess and begin to act on their potential roles as leaders in obesity prevention.
Keywords: Food and Nutrition; Health and Medicine